Treatment With Therapeutic Bandages to Control Equine Postarthroscopic Tibio-Patellofemoral Swelling - Mattos, Luiz Henrique Lima [UNESP]; Yamada, Ana Lúcia Miluzzi [UNESP]; dos Santos, Vitor Hugo [UNESP]; Hussni, Carlos A. [UNESP]; Rodrigues, Celso Antonio [UNESP]; Watanabe, Marcos Jun [UNESP]; Alves, Ana Liz Garcia [UNESP] (Elsevier, 2017)
The aim of this study was to evaluate the effect of therapeutic bandages, the Kinesio Taping Method (KTM), in controlling swelling following arthroscopic tibio-patellofemoral surgery in horses. In vivo experimental study was studied. Twelve horses undergoing experimental tibio-patellofemoral arthroscopy were divided into two groups: six animals in the control group (CG) (without tape) and six animals in the treatment group (TG) that received therapeutic bandages based on the KTM. All of the horses were evaluated by thermography of the lateral and cranial aspect of the joint as well as by a perimeter assessment of the tibio-patellofemoral joint. The TG showed greater control of postoperative swelling with a significant reduction in swelling after 24 hours of treatment compared to the CG staying up to 72 hours, but there were no significant differences in temperature based on the thermography. In this study, which was unprecedented in horses, the use of therapeutic bandages resulted in a significant reduction in postoperative swelling of tibio-patellofemoral arthroscopy in horses compared with CG. Although often employed in human rehabilitation, this therapy is potentially beneficial for veterinary rehabilitation, specifically in horses.
Keywords: Arthroscopy; Equine; Kinesio taping; Therapeutic bandage; Tibio-patellofemoral